Cellulose Nanocrystals in Cancer Diagnostics and Treatment - Lugoloobi, Ishaq; Maniriho, Hillary; Jia, Liang; Namulinda, Tabbisa; Shi, Xiangyang; Zha, Yili (Journal of Controlled Release, 2021)
Cancer is currently a major threat to public health, being among the principal causes of death to the global population. With carcinogenesis mechanisms, cancer invasion, and metastasis remaining blurred, cancer diagnosis and novel drug delivery approaches should be developed urgently to enable management and treatment. A dream break-through would be a non-invasive instantaneous monitoring of cancer initiation and progression to fast-track diagnosis for timely specialist treatment decisions. These innovations would enhance the established treatment protocols, unlimited by evasive biological complexities during tumorigenesis. It is therefore contingent that emerging and future scientific technologies be equally biased towards such innovations by exploiting the apparent properties of new developments and materials especially nanomaterials. CNCs as nanomaterials have undisputable physical and excellent biological properties that enhanced their interest as biomedical materials. This article therefore highlights CNCs utility in cancer diagnosis and therapy. Their extraction, properties, modification, in-vivo/in-vitro medical applications, biocompatibility, challenges and future perspectives are precisely discussed.
Keywords: Cellulose nanocrystals (CNCs); Preparation; Modification; Cancer therapy; Biocompatibility